Older Patients' Perspectives on Quality of Serious Illness Care in Primary Care. (October 2018) - Abu Al Hamayel, Nebras.; Isenberg, Sarina R.; Hannum, Susan M.; Sixon, Joshua; Smith, Katherine Clegg.; Dy, Sydney M.
Background: Despite increased focus on measuring and improving quality of serious illness care, there has been little emphasis on the primary care context or incorporation of the patient perspective. Objective: To explore older patients' perspectives on the quality of serious illness care in primary care. Design: Qualitative interview study. Participants: Twenty patients aged 60 or older who were at risk for or living with serious illness and who had participated in the clinic's quality improvement initiative. Methods: We used a semistructured, open-ended guide focusing on how older patients perceived quality of serious illness care, particularly in primary care. We transcribed interviews verbatim and inductively identified codes. We identified emergent themes using a thematic and constant comparative method. Results: We identified 5 key themes: (1) the importance of patient-centered communication, (2) coordination of care, (3) the shared decision-making process, (4) clinician competence, and (5) access to care. Communication was an overarching theme that facilitated coordination of care between patients and their clinicians, empowered patients for shared decision-making, related to clinicians' perceived competence, and enabled access to primary and specialty care. Although access to care is not traditionally considered an aspect of quality, patients considered this integral to the quality of care they received. Patients perceived serious illness care as a key aspect of quality in primary care. Conclusions: Efforts to improve quality measurement and implementation of quality improvement initiatives in serious illness care should consider these aspects of care that patients deem important, particularly communication as an overarching priority.